The Involvement of ALPK3 in Hypertrophic Cardiomyopathy in East Asia - Dai, Jiaqi; Li, Ke; Huang, Man; Sun, Yang; Liu, Hao; Li, Zongzhe; Chen, Peng; Wang, Hong; Wu, Dongyang; Chen, Yanghui; Xiao, Lei; Wei, Haoran; et al. (Frontiers in Medicine, 2022)
Objective ALPK3 is associated with a recessive form of pediatric cardiomyopathy accompanied by musculoskeletal and craniofacial abnormalities. Heterozygous truncating variants in this gene (ALPK3tv) have recently been confirmed as a cause of autosomal dominant hypertrophic cardiomyopathy (HCM). Whether ALPK3 is also implicated in HCM in East Asia and the effect of missense variants in ALPK3 on HCM remains unresolved. Methods We compared the frequency of rare deleterious variants in ALPK3 in a study cohort comprised of 793 HCM cases of East Asian descent to that in the controls subset of Genome Aggregation Database (gnomAD). Gene burden test was used to assess this association. The involvement of these variants in HCM was further validated by independent cohort. The clinical characteristics and prognoses of these carriers were compared with sarcomere-positive and negative patients. Results Rare deleterious variants in ALPK3 were significantly enriched in HCM compared with gnomAD controls (truncating: 4/793 vs. 4/4523, P = 0.02; missense: 25/793 vs. 46/4523, P = 2.56e-5). Replication in an independent cohort provided more supporting evidence. Further comparisons revealed that ALPK3 carriers displayed more severe hypertrophy in interventricular septum (IVS) and apex, as well as greater maximal left ventricular wall thickness, relative to sarcomere negatives. Conclusion Heterozygous rare variants in ALPK3, both missense and truncating variants, are associated with HCM in East Asians.